Plasma urea cycle metabolite levels and the risk of moyamoya disease - Yu, Xiaofan; Ge, Peicong; Zhai, Yuanren; Liu, Wei; Zhang, Qian; Ye, Xun; Liu, Xingju; Wang, Rong; Zhang, Yan; Zhao, Jizong; Zhang, Dong (Frontiers in Neuroscience, 2023)
Urea cycle metabolites are expected to be the biomarkers for cerebrovascular diseases.However, effects of circulating urea cycle metabolites on the risk of MMD and its subcategories remains unclear. Aim of this study was to prospectively investigate the association between plasma urea cycle metabolites and the risk of MMD and its subcategories.We measured plasma urea cycle metabolites levels for 360 adult MMD patients and 89 matched healthy controls. Clinical and laboratory characteristics were not measured by ourselves, but collected from the medical record. The study was conducted from July 2020 to December 2021.After multivariate adjustment, the risk of MMD increased with each increment in ornithine level (per natural log [ornithine] increment: OR, 3.893; 95% CI, 1.366-11.090). The risk of MMD decreased with each increment in arginine level (per natural log [arginine] increment: OR, 0.109; 95% CI, 0.028-0.427), urea level (per natural log [urea] increment: OR, 0.261; 95% CI, 0.072-0.940), and global arginine bioavailability ratio (GABR) level (per natural log [GABR] increment: OR, 0.189; 95% CI, 0.074-0.484). The addition of plasma arginine (integrated discrimination improvement: 1.76%, p = 0.021) or GABR (integrated discrimination improvement:1.76%, p = 0.004) to conventional risk factors significantly improved the risk reclassification for the risk of MMD.Plasma ornithine levels were positively associated with the risk of MMD. On the contrary, the levels of arginine, urea, and GABR were inversely related to the risk of MMD. Plasma urea cycle metabolites might be potential biomarkers for the risk of MMD.